Wintertime subarctic new particle formation from Kola Peninsula sulfur emissions - M. Sipilä (Copernicus Publications, 2021)
The metallurgical industry in the Kola Peninsula, north-west Russia, form, after Norilsk, Siberia, the second largest source of air pollution in the Arctic and subarctic domain. Sulfur dioxide (SO2) emissions from the ore smelters are transported to wide areas, including Finnish Lapland. We performed investigations on concentrations of SO2, aerosol precursor vapours, aerosol and ion cluster size distributions together with chemical composition measurements of freshly formed clusters at the SMEAR I station in Finnish Lapland relatively close (∼ 300 km) to the Kola Peninsula industrial sites during the winter 2019–2020. We show that highly concentrated SO2 from smelter emissions is converted to sulfuric acid (H2SO4) in sufficient concentrations to drive new particle formation hundreds of kilometres downwind from the emission sources, even at very low solar radiation intensities. Observed new particle formation is primarily initiated by H2SO4–ammonia (negative-)ion-induced nucleation. Particle growth to cloud condensation nuclei (CCN) sizes was concluded to result from sulfuric acid condensation. However, air mass advection had a large role in modifying aerosol size distributions, and other growth mechanisms and condensation of other compounds cannot be fully excluded. Our results demonstrate the dominance of SO2 emissions in controlling wintertime aerosol and CCN concentrations in the subarctic region with a heavily polluting industry.